Registration of single quantum dots using cryogenic laser photolithography - Lee, K; Green, A; Taylor, R; Sharp, D; Scrimgeour, J; Roche, O; Na, J; Jarjour, A; Turberfield, A; Brossard, F; Williams, D; Briggs, G (American Institute of Physics, 2006)
We have registered the position of single InGaAs quantum dots using a cryogenic laser photolithography technique. This is an important advance towards the reproducible fabrication of solid-state cavity quantum electrodynamic devices, a key requirement for commercial exploitation of quantum information processing. The quantum dot positions were registered with an estimated accuracy of 50 nm by fabricating metal alignment markers around them. Photoluminescence spectra from quantum dots before and after marker fabrication were identical except for a small redshift (~1 nm), probably introduced during the reactive ion etching.